A review on mechanical properties and deterioration mechanisms of FRP bars under severe environmental and loading conditions. (November 2022) - Feng, Guangyan; Zhu, Deju; Guo, Shuaicheng; Rahman, Md Zillur; Jin, Zuquan; Shi, Caijun
Abstract: Rebar corrosion is the most common durability issue in reinforced concrete structures, and replacing steel rebar with fiber-reinforced polymer (FRP) bar can effectively resolve the corrosion issue. Furthermore, it can serve as an appropriate substitute for steel rebar due to its lightweight, high strength, and good corrosion resistance. However, the mechanical performance of FRP bars can still deteriorate under severe environmental and loading conditions. As a result, it is essential to understand the deterioration mechanisms of FRP bars and enhance their durability performance. This study first critically reviews the influences of reinforcement, resin, and bar diameter on the mechanical properties of FRP bars in alkaline solution. The degradation of the mechanical properties of FRP bars is further evaluated in water, seawater, and alkaline solution. The influences of wet-dry and freeze-thaw cycles on the FRP bar degradation are also discussed. The degradation mechanisms are analyzed considering the coupling effect of exposure conditions, temperatures, concrete wrappings, and loadings. Then, currently available prediction models for the long-term durability of FRP bars are summarized. Finally, some suggestions for future works are proposed, and concluding remarks are made. This study can provide insight into FRP bars in severe service conditions for their research and application.